Functions of Natural Organic Matter in Changing Environment - Xu, Jianming; Wu, Jianjun; He, Yan.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Functions of Natural Organic Matter in Changing Environment presents contributions from the 16th Meeting of the International Humic Substances Society (IHSS 16) held in Hangzhou, China on September 9-14, 2012. It provides a comprehensive and updated research advance in the field of characterization, function, application of humic substances (HS) and natural organic matter (NOM) in environment, agriculture, and industry. A broad range of topics are covered: i) formation, structure and characteristics of HS and NOM; ii) HS/NOM and carbon sequestration; iii) HS/NOM and biogeochemical cycling of nutrients; iv) HS/NOM and the environmental processes of toxic elements and anthropogenic organics; v) HS/NOM, naturally occurring and engineered nanoparticles; vi) HS/NOM, biodiversity and ecosystem health; vii) HS/NOM in water and water treatment; viii) characterization and function of biochar in the environment; and ix) industrial products and application of HS. The book will be an invaluable reference for chemists, biologists, environmental scientists, ecologists, soil scientists, water scientists, agronomists, global change researchers and policy makers. Jianming Xu is Professor and Director at the Institute of Soil and Water Resources and Environmental Science, Zhejiang University, Hangzhou, China. Jianjun Wu is Professor at the Institute of Soil and Water Resources and Environmental Science, Zhejiang University, Hangzhou, China. Yan He is Associate Professor at the Institute of Soil and Water Resources and Environmental Science, Zhejiang University, Hangzhou, China.
Formation, Structure and Characteristics of HS and NOM -- HS/NOM and Carbon Sequestration -- HS/NOM and Biogeochemical Cycling of Nutrients -- HS/NOM and the Environmental Processes of Toxic Elements and Anthropogenic Organics -- HS/NOM, Naturally Occurring and Engineered Nanoparticles -- HS/NOM, Biodiversity and Ecosystem Health -- HS/NOM in Water and Water Treatment -- Characterization and Function of Biochar in the Environment -- Industrial Products and Application of HS.
Keywords: Environmental sciences; Microbiology; Ecology; Environmental chemistry; Environmental toxicology; Soil conservation; Environment; Soil Science & Conservation; Microbiology; Applied Microbiology; Environmental Chemistry; Ecotoxicology; Ecology